2011
DOI: 10.1051/0004-6361/201016115
|View full text |Cite
|
Sign up to set email alerts
|

Lunar mare single-scattering, porosity, and surface-roughness properties with SMART-1 AMIE

Abstract: A novel shadowing and coherent-backscattering model is utilized in the analysis of the single-scattering albedos and phase functions, local surface roughness, and regolith porosity of specific lunar mare regions imaged by the AMIE camera (Advanced Moon micro-Imager Experiment) onboard ESA SMART-1 mission. Shadowing due to the regolith particles is accounted via ray-tracing computations for densely-packed particulate media with a fractional-Brownian-motion interface with free space. The shadowing modeling allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…[5] Recent analysis of the LRO data for highland regions by Hapke et al [2012] showed that the coherent backscatter enhancement contributes nearly 40% in the UV, increasing to over 60% in the red. A significant contribution of this enhancement to the BOE at a < 10 is also assessed in Muinonen et al [2011]. Thus, several authors concluded that the BOE contains a large component of coherent backscattering.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…[5] Recent analysis of the LRO data for highland regions by Hapke et al [2012] showed that the coherent backscatter enhancement contributes nearly 40% in the UV, increasing to over 60% in the red. A significant contribution of this enhancement to the BOE at a < 10 is also assessed in Muinonen et al [2011]. Thus, several authors concluded that the BOE contains a large component of coherent backscattering.…”
Section: Introductionmentioning
confidence: 87%
“…A significant contribution of this enhancement to the BOE at α < 10° is also assessed in Muinonen et al . []. Thus, several authors concluded that the BOE contains a large component of coherent backscattering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To compare the same area covered from multiple observations with different observation geometries and to compare data taken from different instruments, photometric corrections are needed to normalize the reflectance as if it is measured in the same observation geometry. Numerous photometric analyses have been performed on the Moon using the spectral data from ground-based, orbital (i.e., Lunar Orbiter, SMART-1, Kaguya, Chang'E, Chandrayann-1, and LRO itself), and in situ (e.g., the Yutu Rover of the Chang'E-3 lunar mission) observations, covering wavelengths from UV, visible (VIS), and near infrared (NIR; Besse et al, 2013;Buratti et al, 2011;Hapke et al, 2012;Hicks et al, 2011;Hillier et al, 1999;Jin et al, 2015;Kieffer & Stone, 2005;McEwen, 1996;Muinonen et al, 2011;Robinson & Jolliff, 2002;Sato et al, 2014;Wilkman et al, 2014;Wu et al, 2013;Yokota et al, 2011). Notable FUV observations in particular, prior to LRO, have been performed by Apollo-17 Ultraviolet Spectrometer, Hopkins Ultraviolet Telescope, and Galileo-Ultraviolet Spectrometer (Hendrix, 1996;Henry et al, 1995;Lucke et al, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Further numerical modeling techniques were developed by Muinonen et al (2011) and Wilkman et al (2014a) with the lunar mare data acquired by SMART-1/AMIE. They employed a numerical approach to solve for the shadowing function resulted from the surface roughness using ray-tracking technique with the LS sphere as the auxiliary tool.…”
Section: Muinonen Rt-cb Modelmentioning
confidence: 99%